Deregulation and the determinants of entry: Evidence from the German interurban bus industry - Niklas S. Dürr; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Two years after the deregulation of the German interurban bus industry in January 2013, two new entrants emerged as market leaders: MeinFernbus (MFB) and FlixBus (FB). We use a comprehensive route-level data set to investigate the determinants of route entry for both providers. Applying survival models, we find that both companies show an increased probability to enter populous, centrally located routes with large shares of young inhabitants; however, they both avoid entries into routes including an airport or with low quality rail connection. Furthermore, both market leaders refrain from entering small and medium-sized routes in which another provider is already operating. In large markets, however, they both show an increased entry probability independent of the presence of a competitor.
urn:nbn:de:bsz:180-madoc-414040
Keywords: L92; L11; L20; C41; M20; R41; 330; deregulation; entry; industry dynamics; interurban buses; survival analysis